The politics of elegy: Henri IV of France by Villamediana, Quevedo, Góngora, and Rubens. Issue 1 (June 2017) - Andrews, Jean
Abstract : This article examines Franco-Spanish political relations in the period from 1610 to 1625 as represented in Spanish poetry and paintings produced in Spain or in the Spanish theatre of influence. The early seventeenth century was a time of cautious rapprochement and powerful underlying tensions between these nations. Two events of major significance are explored: the assassination of Henry IV of France in May 1610 and the reciprocal Bourbon-Habsburg marriages of 1615. The assassination is reflected in funeral sonnets by Góngora, Quevedo, Lope de Vega, and the Conde de Villamediana, while Henri himself and the marriages were portrayed by Rubens, envoy of the Infanta Isabel Clara Eugenia, Governor of Flanders, in his series on the life of Henri's widow, Marie de Médicis (1625). This article considers the interplay of poetry and politics in these two complementary art forms and their effect on the legacy of Henri IV in Habsburg lands.